Generation of photon vortex by synchrotron radiation from electrons in Landau states under astrophysical magnetic fields - Tomoyuki Maruyama; Takehito Hayakawa; Toshitaka Kajino; Myung-Ki Cheoun (Physics Letters B, 2022)
We explore photon vortex generation in synchrotron radiations from a spiral moving electron under a uniform magnetic field along z-axis using Landau quantization. The obtained wave-function of the photon vortices is the eigen-state of the z-component of the total angular momentum (zTAM). In m-th harmonic radiations, individual photons are the eigen-state of zTAM of mħ. This is consistent with previous studies. Using the presently obtained wave-functions we calculate the decay widths and the energy spectra under extremely strong magnetic fields of 1012–1013 G, which are observed in astrophysical objects such as magnetized neutron stars and jets and accretion disks around black holes. The result suggests that photon vortices are predominantly generated in such objects. Although they have no coherency it is expected that photon vortices from the universe are measured using a detector based upon a quantum effect in future. This effect also affects to stellar nucleosynthesis in strong magnetic fields.